The expanding role of fludarabine in hematologic malignancies - Keating, M.J.; O'Brien, S.; Robertson, L.E.; Kantarjian, H.; Dimopoulos, M.; McLaughlin, P.; Cabanillas, F.; Gregoire, V.; Ying-Yang, L.; Gandhi, V.; Estey, E.; Plunkett, W. (Leukemia and Lymphoma, 1994)
The major clinical experience with fludarabine has been obtained in patients with chronic lymphocytic leukemia (CLL). In the initial studies in previously treated patients with CLL, the complete and partial response rate (CR + PR) was over 50% and in previously untreated patients with CLL, a CR + PR rate of 75-80% was noted with or without the addition of prednisone. Subsequent clinical trials have also demonstrated major activity with fludarabine in Waldenstrom's macroglobulinemia. Fludarabine was noted to be an active agent in indolent lymphoma in phase I/II studies. Approximately 60% of patients with follicular lymphoma respond to fludarabine when it is administered as a single agent. Many of these remissions are complete remissions despite patients having received extensive prior therapy. Combination programs are being developed for application in CLL and indolent lymphoma. Because of the activity of fludarabine in inhibiting DNA repair, it has been combined with cisplatinum and cytosine arabinoside and plans are in place to explore the radiation sensitizing effect of fludarabine in clinical trials. A combination of fludarabine plus ara-C is now being used in patients with acute myelogenous leukemia (AML) and myelodysplastic syndrome (MDS) and a combination of fludarabine, ara-C, and G-CSF (FLAG) has been combined with idarubicin for the management of these conditions. Many of these activities of fludarabine are associated with its interaction with many enzymes which are important in DNA and RNA metabolism and in DNA repair. It is anticipated that these actions will be explored in a wider range of studies subsequently. © 1994 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: Acute myelogenous leukemia; Chronic lymphocytic leukemia; Fludarabine; Low grade lymphoma; Lymphoid malignancies; Myelodysplastic syndrome; Radiation sensitizer